2016
DOI: 10.1080/09687637.2016.1252316
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of intravenous drug users in London towards the provision of drug consumption rooms

Abstract: Aims: The study investigated the attitudes of intravenous drug users (IDUs) towards the provision of drug consumption rooms (DCRs) in the UK and their willingness to use DCRs. Methods:Participants were 90 methadone-maintained outpatients recruited from a London clinic. A questionnaire asked about their willingness to use a DCR, their views on various rules commonly-implemented by DCRs, and how they believed DCRs might impact on the drug-taking behaviours of drug users and their peers. Findings: A large majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…In the context of proposals to establish the UK's first DCR in Glasgow, we found that the vast majority (75%) of PWID in Scotland expressed willingness to use a DCR. The high level of willingness to use a DCR among PWID in Scotland is consistent with other studies which have been conducted in cities elsewhere in the UK (London and Leeds) (84-89%) ( Butler et al., 2018 ; Hunt, Lloyd, Kimber, & Tompkins, 2007 ) and in North America (76-87%) ( Bouvier et al., 2017 ; Green et al., 2004 ). Furthermore, studies in cities which have successfully introduced DCRs, such as Vancouver (92%) ( Kerr, Wood, Small, Palepu, & Tyndall, 2003 ) and Melbourne (77%) ( Fry et al., 1999 ) showed similar acceptability rates prior to their introduction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the context of proposals to establish the UK's first DCR in Glasgow, we found that the vast majority (75%) of PWID in Scotland expressed willingness to use a DCR. The high level of willingness to use a DCR among PWID in Scotland is consistent with other studies which have been conducted in cities elsewhere in the UK (London and Leeds) (84-89%) ( Butler et al., 2018 ; Hunt, Lloyd, Kimber, & Tompkins, 2007 ) and in North America (76-87%) ( Bouvier et al., 2017 ; Green et al., 2004 ). Furthermore, studies in cities which have successfully introduced DCRs, such as Vancouver (92%) ( Kerr, Wood, Small, Palepu, & Tyndall, 2003 ) and Melbourne (77%) ( Fry et al., 1999 ) showed similar acceptability rates prior to their introduction.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, we found a positive association between cumulative risk and willingness, with willingness to use a DCR increasing with a higher score in our cumulative risk variable (based on self report of public injecting, cocaine injecting, sharing injecting equipment, re-using injecting equipment and a high injecting frequency). Our results indicate that if a DCR were piloted in Glasgow as proposed, or elsewhere in Scotland, it would likely attract PWID with the greatest risk of drug-related harm, consistent with previous research ( Bouvier et al., 2017 ; Butler et al., 2018 ; Fry et al., 1999 ; Green et al., 2004 ; Wood et al., 2003 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since 2013, an increasing number of papers analysed SIF‐related laws and policies . In 2016 and 2017, a larger number of publications emphasised the need to expand DCRs/SIFs , including studies that examined the willingness to use SIFs/DCRs among people who use drugs (PWUD) , community support for these services and cost‐effectiveness of scaling them up (Figure ). The need for scale‐up was expressed mainly in papers from Canada and from counties where there are no SIFs such as the USA or UK (Figure , Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…International studies, including those conducted in Scotland (Trayner et al, (2020)), have consistently found a high degree of willingness of PWID to use DCRs, particularly those most at-risk of drug-related harm (e.g. Bouvier, Elston, Hadland, Green, and Marshall (2017); Butler, Chapman, and Terry (2018); Hunt, Lloyd, Kimber, and Tompkins (2007)). However, there has been less research investigating public attitudes and support for the introduction and operation of DCR, and little conducted in the UK (Potier, Laprévote, Dubois-Arber, Cottencin, & Rolland, 2014).…”
Section: Introductionmentioning
confidence: 99%